2014
DOI: 10.1016/j.nbd.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β mediated amyloid plaque clearance is independent of CCR2 signaling in the APP/PS1 mouse model of Alzheimer's disease

Abstract: Neuroinflammation is a key component of Alzheimer’s disease (AD) pathogenesis. Particularly, the proinflammatory cytokine interleukin-1 beta (IL-1β) is upregulated in human AD and believed to promote amyloid plaque deposition. However, studies from our laboratory have shown that chronic IL-1β overexpression in the APPswe/PSEN1dE9 (APP/PS1) mouse model of AD ameliorates amyloid pathology, increases plaque-associated microglia, and induces recruitment of peripheral immune cells to the brain parenchyma. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…17 Therefore, we explored whether the increase of CTSB was involved in Mn-induced activation of the NLRP3 inflammasome. NH 4 Cl inhibits the acidification of the lysosome and decreases the expression of CTSB. 50 We found that NH 4 Cl significantly inhibited the Mn-induced increase of CTSB, NLRP3 and cleaved CASP1, and the release of IL1B and IL18, without a significant effect on autophagy-related proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Therefore, we explored whether the increase of CTSB was involved in Mn-induced activation of the NLRP3 inflammasome. NH 4 Cl inhibits the acidification of the lysosome and decreases the expression of CTSB. 50 We found that NH 4 Cl significantly inhibited the Mn-induced increase of CTSB, NLRP3 and cleaved CASP1, and the release of IL1B and IL18, without a significant effect on autophagy-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…< P < 0.05 when compared with the Nlrp3 siRNA Group. the NH 4 Cl caused a significant reduction in protein CTSB levels, attenuating the activation of NLRP3-CASP1 inflammasomes (Fig. 10A, B) as well as the release of IL1B and IL18 (Fig.…”
Section: Mn-induced Release Of Ctsb Triggers Nlrp3-casp1 Inflammasomementioning
confidence: 97%
See 2 more Smart Citations
“…Chemokine ligand 4(CCL4) is overexpressed in APP/PS1 brains and that levels of CCL4 mRNA and protein are positively correlated with the age-related progression of cerebral insoluble Aβ deposition in these mice [48]. Other studies showed that long term over-expression of IL-1β could improve the pathological changes of Aβ, increase the expression of microglia associated with Aβ plagues, and induce the entry of peripheral immune cells into the brain [49].…”
Section: Inflammation Responsementioning
confidence: 99%